Overabundant suburban deer, invertebrates, and the spread of an invasive exotic plant - Jeffrey P. Duguay; Cheryl Farfaras (Wildlife Society Bulletin)
Abstract White‐tailed deer (Odocoileus virginianus) overabundance is a problem of serious concern for wildlife managers. At densities as low as 8 deer/km2, changes in vegetation due to deer feeding patterns have been demonstrated to negatively impact other wildlife species. The Middle Patuxent Environmental Area (MPEA) in Howard County, Maryland, USA, currently supports a deer population of approximately 41 deer/km2. We used an experimental approach to examine how deer overabundance in a suburban environment impacts both vegetation and invertebrates. Ten 20‐m × 20‐m deer exclosures were constructed in the MPEA during the winter–spring of 1999. Vegetation and invertebrate data have subsequently been collected inside the exclosures and areas adjacent to the exclosures (control) during the summers of 1999, 2003, and 2007. There was no initial difference in vegetation variables between exclosure and control plots in 1999 (P > 0.05). Post‐1999, plant species richness was greater in the exclosure than in the control. A multivariate analysis of variance revealed differences (P < 0.001) in vegetation cover variables between exclosures and controls, with a greater percentage of forbs, shrubby vegetation, and taller stems in the exclosure and more grass and exotics in the control. There were few differences in invertebrates between exclosures. The differences observed in vegetation between exclosures is believed to reflect interactions between deer feeding patterns and the invasive Japanese stilt grass (Microstegium vimineum) and unless deer density is reduced, it is likely that the exotic Japanese stiltgrass will continue to increase in abundance and native plant species will decrease. © 2011 The Wildlife Society.